Immunophenotypic features of bone marrow tumor cell in Burkitt lymphoma/leukemia: B-lineage acute lymphoblastic leukemia diagnostics opportunities - I. A. Demina; T. Yu. Verzhbitskaya; S. A. Kashpor; S. A. Plyasunova; M. E. Dubrovina; L. G. Fechina; N. V. Myakova; E. V. Samochatova; A. A. Maschan; A. M. Popov (Онкогематология)
Bone marrow tumor blasts immunophenotyping is an essential part of Burkitt lymphoma/leukemia (BL) and B-cell precursor acute lymphoblastic leukemia (BCP-ALL) differential diagnostics. Nevertheless immunoglobulin heavy and light chains detection on the cell surface could meet several biological and methodological pitfals. Thus the aim of the present study was development of additional BL immunophenotypic criteria. Leukemic blasts antigen profile in 21 BL cases and 84 children with BCP-ALL was compared in a retrospective way. Antigen expression patterns in BL and BCP-ALL were significantly different. It was shown that even in cases with weak immunoglobulin M expression these two tumor types could be distinguished well by complex immunophenotype analysis. In present study all cases of CD34-negative B-lineage ALL without myeloid coexpression and with high CD20-positive cells proportion belonged to BL.